High-voltage CMOS active pixel sensor - Peric, Ivan; Andreazza, Attilio; Augustin, Heiko; Barbero, Marlon; Benoit, Mathieu; Casanova, Raimon; Ehrler, Felix; Iacobucci, Giuseppe; Leys, Richard; Meneses González, Annie; Pangaud, Patrick; Prathapan, Mridula; et al. (IEEE journal of solid state circuits, 2021)
The high-voltage CMOS (HVCMOS) sensors are a novel type of CMOS active pixel sensors for ionizing particles that can be implemented in CMOS processes with deep n-well option. The pixel contains one sensor electrode formed with a deep n-well implanted in a p-type substrate. CMOS pixel electronics, embedded in shallow wells, are placed inside the deep n-well. By biasing the substrate with a high negative voltage and by the use of a lowly doped substrate, a depleted region depth of at least 30 $μ \textm$ can be achieved. The electrons generated by a particle are collected by drift, which induces fast detectable signals. This publication presents a 4.2-cm2 large HVCMOS pixel sensor implemented in a commercial 180-nm process on a lowly doped substrate and its characterization.
Gesehen am 13.10.2021